Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/bio.3702
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐binding activity and cytotoxic and cell‐cycle arrest properties of some new coumarin derivatives: a multispectral and computational investigation

Abstract: Coumarins are the most important class of natural compounds found widely in various plants. Many coumarin derivatives with different biological and pharmacological activities have been synthesized. In this study, the antiapoptotic and cytotoxic effects and DNA-binding properties of some synthetic coumarin derivatives (4b, 4d, 4f, 4 g (DBP-g), 4 h and 4j) against K562 cell lines were investigated using different techniques. MTT assay indicated that the DBP-g compound was more active than other derivatives, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…The alternation in the absorption spectra at maximum wavelength caused by interaction with small molecules plays an important role as it provides information about the ligand’s binding mode, which is either a groove binder or an intercalator. According to the recent research, enhancement in intensity or a red shift is observed when small molecules interact through groove binding mode, whereas intercalation of small molecules into the DNA base pairs imparts intensity reduction or a blue shift …”
Section: Resultsmentioning
confidence: 99%
“…The alternation in the absorption spectra at maximum wavelength caused by interaction with small molecules plays an important role as it provides information about the ligand’s binding mode, which is either a groove binder or an intercalator. According to the recent research, enhancement in intensity or a red shift is observed when small molecules interact through groove binding mode, whereas intercalation of small molecules into the DNA base pairs imparts intensity reduction or a blue shift …”
Section: Resultsmentioning
confidence: 99%
“…We undertook molecular docking using the DNA oligonucleotide 1DNE to investigate the mechanism that might allow the formation of DNA–PHMG-Cl complexes. 1DNE has been previously used in several studies to investigate the interaction of various ligands with DNA [ 39 , 40 , 41 ]. As we were interested in identifying PHMG-Cl interactions in both AT- and CG-rich regions, we modeled PHMG-Cl as a dimer following the approach used in studying DNA–PHMB dimer interactions [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…We undertook molecular docking using the DNA oligonucleotide 1DNE to investigate the mechanism which might allow the formation of DNA -PHMG-Cl complexes. 1DNE has been previously used in several studies to investigate the interaction of various ligands with DNA [35][36][37]. As we were interested in identifying PHMG-Cl interactions in both AT and CG-rich regions, we modelled PHMG-Cl as a dimer following the approach used in studying DNA -PHMB dimer interactions [38].…”
Section: Dna Docking Assaymentioning
confidence: 99%